1985
DOI: 10.1017/s0022112085002178
|View full text |Cite
|
Sign up to set email alerts
|

Wall-layer structure and drag reduction

Abstract: When drag-reducing additives are confined entirely to the linear sublayer of a turbulent channel flow of water, both the spanwise spacing and bursting rate of the wall-layer structure are the same as those for a water flow and there is no evidence of drag reduction. Drag reduction is measured downstream of the location where the additives injected into the sublayer begin to mix in significant quantities with the buffer region (10 < y+ < 100)The superscript + denotes a dimensionless quantity scaled with the kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(54 citation statements)
references
References 15 publications
(18 reference statements)
9
45
0
Order By: Relevance
“…Donohue et al 22 examined the effects of polymers on turbulent structures by using the visualization technique; they reported that the streaking spacing and bursting rates in drag-reducing flow are different from that in the Newtonian flow, i.e., the average nondimensional spacing between streaks linearly increases with increasing DR and the viscous sublayer was more stable when polymer solutions were present. A suppression of the burst process and an increment of streak spacing were also reported by Berman 16 and Tiederman et al 23 However, Luchik and Tiederman 19 found that the method for deducing the time between bursts was not accurate in these experiments because they did not marked and counted all of these events. Thus, the flow visualization revealed some important phenomena, but a lack of measure of the corresponding turbulent velocity field limits the interpretation.…”
Section: Introductionsupporting
confidence: 66%
“…Donohue et al 22 examined the effects of polymers on turbulent structures by using the visualization technique; they reported that the streaking spacing and bursting rates in drag-reducing flow are different from that in the Newtonian flow, i.e., the average nondimensional spacing between streaks linearly increases with increasing DR and the viscous sublayer was more stable when polymer solutions were present. A suppression of the burst process and an increment of streak spacing were also reported by Berman 16 and Tiederman et al 23 However, Luchik and Tiederman 19 found that the method for deducing the time between bursts was not accurate in these experiments because they did not marked and counted all of these events. Thus, the flow visualization revealed some important phenomena, but a lack of measure of the corresponding turbulent velocity field limits the interpretation.…”
Section: Introductionsupporting
confidence: 66%
“…Similar to other drag-reduction techniques, such as polymer injection [18,19,27,28], the oscillating wall motion brings about an increment of the average streak spacing λ + oscill , 5 as seen in figure 10 and in table 2. A reduction of friction of about 40% goes together with an increment of streaks' spacing of about one-third when values are scaled with the relative inner variables, while the distance doubles in physical dimensions.…”
Section: Jot 5 (2004) 024mentioning
confidence: 77%
“…Once the bubble sheet was generated, it was distorted by the turbulence and then lit by the laser plane. For the analysis of the overhead-view images, a definition of low-speed streak was adopted following the works by Oldaker and Tiederman [18] and by Tiederman et al [19]. A low-speed streak was recognized as a clearly identifiable single longitudinal structure of bubbles with streamwise length at least three times the apparent average streaks' spacing.…”
Section: Flow Visualization Setup and Proceduresmentioning
confidence: 99%
“…Observations of drag-reducing fluids indicate that, at least near the onset Reynolds number for drag reduction, the effects of the polymer are confined primarily to the near-wall buffer layer, 1,[5][6][7][8] which is the most important region for the production and dissipation of turbulent energy. 9 From experia)…”
Section: Introductionmentioning
confidence: 99%